A comment on the presentation and testing of CALGO codes and a remark on algorithm 639 To integrate some infinite oscillating tails. - Hopkins, Tim (ACM transactions on mathematical software.)
We report on a number of coding problems that occur frequently in published CALGO software and are still appearing in new algorithm submissions. Using Algorithm 639 as an extended example, we describe how these types of faults may be almost entirely eliminated using available commercial compilers and software tools. We consider the levels of testing required to instil confidence that code performs reliably. Finally, we look at how the source code may be re-engineered, and thus made more maintainable, by taking account of advances in hardware and language development.